2005
DOI: 10.1021/la047368k
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Nonspherical Microparticles Using Microfluidics

Abstract: The controlled synthesis of nonspherical microparticles using microfluidics processing is described. Polymer droplets, formed by shearing a photopolymer using a continuous water phase at a T-junction, were constrained to adopt nonspherical shapes by confining them using appropriate microchannel geometries. Plugs were obtained by shearing the polymer phase at low shear rates, while disks were obtained by flattening droplets using a channel of low height. The nonspherical shapes formed were permanently preserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
386
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(390 citation statements)
references
References 22 publications
1
386
0
3
Order By: Relevance
“…It is the elaborate chip design that allowed researchers not only to miniaturize microchannel emulsification reactors and prepare narrowly monodisperse spherical beads but also to achieve unprecedented control over structure and shape of particles. This unique capability of control resulted in the realization of perfectly controlled multiple emulsions [136][137][138][139][140][141][142][143][144][145], Janus particles [146][147][148][149][150][151][152][153][154][155][156], regular nonspherical shapes [157][158][159][160][161][162][163][164][165][166] and even gas bubbles [167][168][169][170][171], almost all of which were impossible to achieve before.…”
Section: Microfluidics: the Ultimate Controlmentioning
confidence: 99%
“…It is the elaborate chip design that allowed researchers not only to miniaturize microchannel emulsification reactors and prepare narrowly monodisperse spherical beads but also to achieve unprecedented control over structure and shape of particles. This unique capability of control resulted in the realization of perfectly controlled multiple emulsions [136][137][138][139][140][141][142][143][144][145], Janus particles [146][147][148][149][150][151][152][153][154][155][156], regular nonspherical shapes [157][158][159][160][161][162][163][164][165][166] and even gas bubbles [167][168][169][170][171], almost all of which were impossible to achieve before.…”
Section: Microfluidics: the Ultimate Controlmentioning
confidence: 99%
“…3 Recently, microdroplet technology has been used as microreactors for chemical analysis and protein crystallization, 5,6 as molds for curing polymeric microspheres. 7,8 Furthermore, programmable fluidic assays for sampling glucose concentration of human physiological fluids 9 and DNA analysis 10 have been individually demonstrated using microdroplet system. As samples=reagents are confined in droplets so that sample dilution caused by Taylor dispersion 11 can be avoided, and mixing performance can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several research groups have reported synthesis of polymer particles in microfluidic reactors (Cohen et al 2001;Dendukuri et al 2005;Jeong et al 2005;Lewis et al 2005;Loscertales et al 2002;Nie et al 2005Nie et al , 2006Nisisako et al 2004;Seo et al 2005aSeo et al , 2005bTakeuchi et al 2005;Utada et al 2005;Xu et al 2005;Zhang et al 2006). The syntheses included a two-step process: (1) microfluidic emulsification of monomer or polymeric fluids, and (2) subsequent in-situ (on chip) solidification of the droplets by means of polymerization, gelation, or solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…The syntheses included a two-step process: (1) microfluidic emulsification of monomer or polymeric fluids, and (2) subsequent in-situ (on chip) solidification of the droplets by means of polymerization, gelation, or solvent evaporation. Microfluidic methods allowed for the production of particles with diameters from several micrometers to hundreds of micrometers, polydispersities below 5%, and shapes and morphologies that were not achievable in the conventional synthesis of colloids (Nisisako et al 2004;Xu et al 2005;Nie et al 2005Nie et al , 2006Dendukuri et al 2005). Such particles have a broad range of potential applications including their use as ion exchange resins, spacers, calibration standards, and carriers for drugs, nutrition, pharmaceutical, and cosmetics agents.…”
Section: Introductionmentioning
confidence: 99%